Effects of Client-Centered Occupational Therapy on Behavioral Psychological Symptoms, Social Interaction, Occupational Performance, Quality of Life, and Caregiver Burden among the Individuals with Dementia. Issue 2 (3rd April 2023) - Kwon, Mi-Hwa; Kim, Su-Kyoung
Abstract: This study aimed to verify the effects of client-centered occupational therapy on individuals with dementia. Twenty participants were randomly assigned to an experimental group (client-centered occupational therapy) and a control group (general occupational therapy). A pretest, post-test, and follow-up tests were used to compare the effects of the intervention. The experimental group had significant changes in all variables, and the control group showed significant differences in verbal social interaction, quality of life, and burden of caregivers ( p  < 0.05). As a result of repeated measurement variance analysis, it was found that there was a significant effect within the group except for the NPI-Q distress items ( p  < 0.05), but the effect was not verified in all areas between the groups. Client-centered customized occupational therapy can be more effective than general occupational therapy in problem behavior, social interaction, quality of life, caregiver burden, and occupational performance of individuals with dementia.